دراسة مورفولوجية وبيو كيميائية لبعض أصناف الرمان المزروع Punica granatum في محافظة اللاذقية - سلمان, يحيى; حليمة, لينا (Latakia University Journal -Biological Sciences Series, 2018)
هدفت الدراسة الى مقارنة الخصائص البيو كيميائية والمورفولوجية لخمسة أصناف من الرمان المزروع في عدة مناطق بمحافظة اللاذقية. تمَ تقييم الخصائص التالية: وزن الثمرة، عدد البذور(الحبات) في الثمرة، وزن القشرة، نسبة المواد الصلبة الذائبة الكلية، الحموضة الكلية كنسبة مئوية، فيتامين Cمغ/ 100مل، نسبة السكريات الأحادية. تراوحت قيم وزن الثمرة بين 336,85- 484,77غ، ووزن القشرة بين 127,85-93,84غ، ووزن العصير كان بين 79,33-151,66غ، ونسبة السكريات الأحادية بين 3,64- 12,4%. تراوحت قيمة المواد الصلبة الذائبة الكلية كنسبة مئوية بين 14,5- 16,5 %، بينما نسبة الحموضة الكلية كانت بين 0,35 -1,32%، أما قيمة فيتامين C كانت بين 11,5- 14,5مغ/ 100مل عصير. The aim of study was to compare the physicochemical and morphological properties of Five pomegranate cultivars grown in different region of latakia. Properties included: fruit fresh weight,number of arils per fruit, peel weight, soluble solids (TSS), titratable acidity (TA)vitamin, reducing sugar . Fruit weight ranged from(336.8 -484.77 g), peel weight of the fruit was recorded from 93,84 to 127,85g, juice weight was( 69,33-151,66 g) and reducing sugars ranged between (3.64 -12.4 %). total soluble solid ranged from( 14.5- 16.5) % and titratable acidity ranged between( 0.358- 1.321%)in pomegranate juices.vitamin C content also ranged between 11.5- 14.5 mg\100 ml).